Assessing differential expression profiles and modeling allele-specific expression in leaves of Saccharum accessions contrasting in biomass production - Correr, Fernando Henrique (2021)
Sugarcane is one of the most important crops worldwide due to its main products - sugar and ethanol -, the reuse of byproducts and the innovation capability of the agroindustry. It offers the potential for a more profitable and sustainable production, which can be accomplished by developing high-yielding cultivars. For that reason, traits other than the sucrose content in culms should also be explored. The so-called energy cane has recently moved the attention of breeding programs towards biomass-related traits such as fiber content and tillering capacity. The genetic variation associated with these traits can be enhanced with other Saccharum accessions that have not yet been explored by breeders. In addition, studies regarding gene expression profiles in diverse groups of genotypes are still limited in the literature. Therefore, we aimed to assess the transcriptomes from leaves of two groups of genotypes - high and low biomass - to identify genes or alleles potentially involved with biomass content. To achieve such goal, genotypes were selected based on their similar phenotypes, regardless of their classification as cultivated or wild. We divided this study into two chapters. In the first chapter, our aim was to identify differentially expressed genes between the biomass groups and to investigate the expression profiles of coexpressed genes. Our results showed that gene expression allowed the study not only of the variability between the contrasting groups, but also the variation within each group. Despite the phenotypic similarity, the high biomass group showed a large variability among its accessions, resulting in many differentially expressed genes (DEGs), many more than in the intergroup comparison. Genes coding for sucrose synthase and proteins related to sucrose synthesis were slightly more expressed in the low biomass group, whereas genes involved with the synthesis of cell wall compounds were significantly less expressed. Interestingly, the coexpression analysis revealed that the expression of genes related to photosynthesis was higher in all hybrids and Saccharum officinarum genotypes. We also showed that different quantification levels have certain influence on the biological insights provided by this kind of study. In the second chapter, we tested for allele-specific expression (ASE) in a subset of the Saccharum samples. These accessions - three hybrids, a S. officinarum and two S. spontaneum - were genotyped via genotyping-by-sequencing, followed by the estimation of ploidy and allelic dosages. We then modeled, for each polymorphism, the probability of expressing the reference allele using a hierarchical Beta-Binomial model, where allelic dosages served as prior information. Results revealed that ASE affects part of the loci assessed in Saccharum. However, no functional term was enriched among genes showing ASE. This study provides the first global view of allele-specific expression in multiple genotypes of sugarcane. Furthermore, the hierarchical model can be used to evaluate ASE in other mixed-ploidy organisms.